Does Melanoma Begin in a Melanocyte Stem Cell? - James D. Hoerter; Patrick Bradley; Alexandria Casillas; Danielle Chambers; Brandon Weiswasser; Lauren Clements; Sarah Gilbert; Albert Jiao (Journal of Skin Cancer)
What is the cellular origin of melanoma? What role do melanocyte stem cells (MSC) and other melanocyte precursors play in the development of melanoma? Are MSCs and other latent melanocyte precursors more susceptible to solar radiation? These and many other questions can be very effectively addressed using the zebrafish model. Zebrafish have a robust regenerative capability, permitting the study of how MSCs are regulated and recruited at specific times and places to generate the pigment pattern following fin amputation or melanocyte ablation. They can be used to determine the effects of environmental radiation on the proliferation, survival, repair, and differentiation of MSCs. Our lab is using zebrafish to investigate how UVA- (320–400 nm) and UVB- (290–320 nm) induced damage to MSCs may contribute to the development of melanoma. A review is given of MSCs in zebrafish as well as experimental techniques and drugs for manipulating MSC populations. These techniques can be used to design experiments to help answer many questions regarding the role of MSCs or melanocyte precursors in the formation of melanoma stem cells and tumors following exposure to UVA/UVB radiation.